2020
DOI: 10.1103/physrevd.101.054002
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of chemical freeze-out parameters in heavy-ion collision experiments

Abstract: We discuss systematic uncertainties in the chemical freeze-out parameters from the χ 2 analysis of hadron multiplicity ratios in the heavy-ion collision experiments. The systematics due to the choice of specific hadron ratios are found to lie within the experimental uncertainties. The variations obtained by removing the usual constraints on the conserved charges show similar behavior. The net charge to net baryon ratios in such unconstrained systems are commensurate with the expected value obtained from the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…It is very important to study the behavior of and due to their relation to map the phase diagram of Quantum Chromodynamics (QCD), though is usually used [ 11 , 12 , 13 , 14 , 15 , 16 ] in the phase diagram. In order to extract and , and study their dependence on energy, we can analyze the ( ) spectra of particles using different models.…”
Section: Introductionmentioning
confidence: 99%
“…It is very important to study the behavior of and due to their relation to map the phase diagram of Quantum Chromodynamics (QCD), though is usually used [ 11 , 12 , 13 , 14 , 15 , 16 ] in the phase diagram. In order to extract and , and study their dependence on energy, we can analyze the ( ) spectra of particles using different models.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there is a renewed interest in studying multiplicity data [84,85]. However, a more prudent approach has been followed in Ref.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In a recent work Ref. [28], we have shown that significant systematic uncertainty may arise in χ 2 analysis due to variation in the chosen set of ratios.…”
Section: Advances In High Energy Physicsmentioning
confidence: 92%
“…This parameter scales the deviation of strange hadrons from a complete equilibrium in the Grand Canonical Ensemble (GCE). In a recent work [28], we have shown that in χ 2 analysis, a larger systematic variation can arise depending on the chosen set of ratios. A conserved-charge-dependent extraction of thermal parameters has been proposed [29], which seems to suitably estimate thermal parameters and predict equilibration in the most central collision.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation